If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-2x + -10) = -2 Reorder the terms: x + -1(-10 + -2x) = -2 x + (-10 * -1 + -2x * -1) = -2 x + (10 + 2x) = -2 Reorder the terms: 10 + x + 2x = -2 Combine like terms: x + 2x = 3x 10 + 3x = -2 Solving 10 + 3x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -2 + -10 3x = -2 + -10 Combine like terms: -2 + -10 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| -6a+3=-3(2a-2) | | 320=-16t^2-4t+322 | | 4-2x=8+6x | | 80000=x+.25x | | 80000=x+25x | | -5x+50-11x=18 | | 85=17n | | 200+.15m=290 | | 57=-19n | | 200+15m=290 | | 200x+15=290 | | 14m=-126 | | .05x+.06(x+1000)=545 | | -5.1d+2.7=-3.9d-2.7 | | 3x=6-1/2x | | (x^4)+(11x^3)+(18x^2)=0 | | 43700=x+0.15x | | .06x+.05(x+1000)=545 | | m-36=16m | | 3x+x-14=0 | | 8x-5(0)=-11 | | 10x-2=5-5x+23 | | X^2+16x+30=2 | | a-5=-18 | | 3(2y+4)=4(2y-.5) | | 5r*56=6x | | 0-6=4(x+5) | | 0=x+14x+48 | | 6u(2-u)=6 | | 6u(2-u)=-7 | | b=b+3a+3c | | 6u(2-u)=7 |